PROPOSING A SHIFT FROM CLASSICAL PENTECOSTAL BIBLE READING AND BACONIAN COMMON SENSE TO A SCIENTIFIC HERMENEUTICS - M. Nel (Acta Theologica)
Although early Pentecostals read the Bible in terms of common sense, it differed from fundamentalists’ use in their theological endeavours. However, by the 1940s, the vast majority of Pentecostals adopted a fundamentalist view of Scriptures. Since the 1990s, Pentecostal scholarship has revisited early Pentecostals’ use of Baconian common sense. In postmodern times, it is important to define a balanced Pentecostal hermeneutic to reconsider the use of Baconian common sense realism in Bible reading practices. A scientifically informed and Spirit-inspired inductive hermeneutic is proposed that emphasises the context of a text, leaving room for the viewpoints of other interpreters and reading in terms of contemporary encounters with God. This will enhance the exegetical process, by enabling the reader to read the Bible for its impact, value and significance.